EVALUASI PROGRAM PEMBERDAYAAN PEREMPUAN MELALUI PELATIHAN MENJAHIT DI SANGGAR KEGIATAN BELAJAR (SKB) UJUNG PANDANG - PRATIWI, NINI; SUPIANA, ILHAM (Universitas Mahasaraswati Mataram, 2021)
Â Â Â Â Â This study was aimed to describe evaluation results of: (1) participantsâ€™ level of satisfaction, (2) participantsâ€™ level of understanding of the material, (3) participantsâ€™ post-training level of implementation, (4) improved success of participants due to the training.Â Â Â Â Â The research type was evaluation research using Kirkpatrickâ€™s Four Level model, which consisted of: Reaction, learning, behavioral, and result levels. The research samples were 20 former training participants. Data was collected by questionnaire, observation, and unstructured interview. Quantitative data was processed with the help of SPSS 21.0 for Windows. Validity of instrument at reaction, learning, behavioral, and result levels used Corrected Item-Total Correlation. Reliability calculation used Alpha formula.Â Â Â Â Â The research result showed that: 1) evaluation of reaction level: the satisfaction to sewing making training in terms of material, tutor, facility, and training method by PAP and PAP was â€œsatisfyingâ€ 2) evaluation of learning level: understanding of material of the participants of making training sewing in terms of understanding of training material by PAP and PAN was â€œMasteringâ€ 3) evaluation of behavioral level: participantsâ€™ implementation after training sewing of making in terms of post-training behavioral aspect by PAP and PAN was â€œimplementingâ€ 4) evaluation of result level: improved resulting competence due to training sewing of making by PAP and PAN was â€œpoorly improvedâ€.